Food composition of greater one-horned rhino (Rhinoceros unicornis) in Chitwan National Park, Nepal - Kuikel, Prayag Raj; Basnet, Khadga (Nepalese Journal of Zoology, 2024)
Greater one-horned rhino (Rhinoceros unicornis) in the Chitwan National Park (CNP), central Nepal exhibit distinct grazing behavior and rely on the riverine forest and grasslands along the Reu, Rapti, and Narayani and their tributaries. In this study, we aimed to investigate the food composition and underlying causes of the abundance of food species for the rhino in CNP. We used quadrat sampling in riverine forests and grassland to examine the cover percent, frequency, and relative importance value of food species for understanding the composition of food and assess the relationship between food composition and the shifting patterns of rhinos from the eastern to the western area of CNP over time. Scan animals used for determining most preferred food species of rhino in CNP. Our findings revealed 23 preferred food species in the rhino's diet, with 7 being grasses, 8 trees, and 8 herbs and shrubs with no significant differences in the food composition of rhinos among different parts of CNP. The grasses species were the most preferred food species contributed 85% in diet of rhino in CNP. These results contribute valuable information for the implementation of effective long-term conservation strategies for large mammals, particularly the rhino in CNP and similar ecosystems.